2013
DOI: 10.1002/grl.50563
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CO2 fertilization on maximum foliage cover across the globe's warm, arid environments

Abstract: [1] Satellite observations reveal a greening of the globe over recent decades. The role in this greening of the "CO 2 fertilization" effect-the enhancement of photosynthesis due to rising CO 2 levels-is yet to be established. The direct CO 2 effect on vegetation should be most clearly expressed in warm, arid environments where water is the dominant limit to vegetation growth. Using gas exchange theory, we predict that the 14% increase in atmospheric CO 2 led to a 5 to 10% increase in green foliage cover in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
438
3
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(492 citation statements)
references
References 39 publications
31
438
3
1
Order By: Relevance
“…The spatial pattern is consistent with previous analyses 15 that posited large absolute LAI increases due to eCO 2 in the tropics, in the absence of temperature, water and nitrogen limitations 16 , and large relative LAI increases due to eCO 2 in arid regions, where eCO 2 is expected to increase the water use efficiency of plants ( Supplementary Fig. 12) 17 . A simple theoretical model 17,18 was used to diagnose the response of leaf level carbon assimilation to the observed 46 ppm increase of CO 2 over the study period, including the effect of vapour pressure deficit trends and stomatal closure.…”
Section: ) D Probability Density Function Of Lai Trends For Gimmssupporting
confidence: 90%
See 1 more Smart Citation
“…The spatial pattern is consistent with previous analyses 15 that posited large absolute LAI increases due to eCO 2 in the tropics, in the absence of temperature, water and nitrogen limitations 16 , and large relative LAI increases due to eCO 2 in arid regions, where eCO 2 is expected to increase the water use efficiency of plants ( Supplementary Fig. 12) 17 . A simple theoretical model 17,18 was used to diagnose the response of leaf level carbon assimilation to the observed 46 ppm increase of CO 2 over the study period, including the effect of vapour pressure deficit trends and stomatal closure.…”
Section: ) D Probability Density Function Of Lai Trends For Gimmssupporting
confidence: 90%
“…12) 17 . A simple theoretical model 17,18 was used to diagnose the response of leaf level carbon assimilation to the observed 46 ppm increase of CO 2 over the study period, including the effect of vapour pressure deficit trends and stomatal closure. This model gave a similar relative response of carbon assimilation to eCO 2 as the ecosystem models did for LAI (Supplementary Section 12).…”
Section: ) D Probability Density Function Of Lai Trends For Gimmsmentioning
confidence: 99%
“…A number of possible factors could be at work but quantifying their relative contribution to these greening trends would require further analysis and is beyond the scope of this study. In part, these greening trends could indicate the effect of CO 2 fertilization on northern vegetation, as seen in modeling studies [85], but such a strong effect is unlikely in cool boreal regions [88]. Changes in permafrost seem to be a factor stimulating greening trends in some subarctic regions.…”
Section: Drivers Of Vegetation Greening and Browning Trendsmentioning
confidence: 92%
“…Studies of historical and future runoff (Gedney et al 2006, Davie et al 2013 often point to increased runoff due to CO 2 -induced increases in water use efficiency (in particular, stomatal closure allowing water to be conserved), which can be observed both at the leaf (Field et al 1995) and ecosystem (Keenan et al 2013) scales. However, a recent analysis of historical observations (Ukkola et al 2016) showed these water savings do not necessarily lead to increased runoff in drier climates due to CO 2 -induced vegetation greening (Donohue et al 2013), which acts to increase vegetation water use at the ecosystem scale. Changes in vegetation water use due to CO 2 as well as climatic factors may play a large, yet to date poorly constrained, role in mediating future water resources.…”
Section: Introductionmentioning
confidence: 99%